A large-scale estimation method for beach slopes using ICESat-2 altimeter: A case study of New Zealand - Nan Xu; Hao Xu; Wenyu Li; Hui Lu; Yongze Song; Jiaqi Yao; Yue Ma; He Ren; Tingting He; Fan Mo; Peng Gong (International Journal of Applied Earth Observations and Geoinformation)
Beach slope is critical for monitoring coastline erosion and assessing coastal vulnerability. However, accurately estimating beach slopes at large scales remains a great challenge due to the dynamic nature of tidal exposure, the limited availability of in-situ topographic data, and the coarse resolution or coverage gaps of traditional DEM products. This study proposed a novel method driven by the Ice, Cloud, and Land Elevation Satellite-2 (ICESat-2) ATL03 product for estimating coastal slopes of sandy beaches by considering ICESat-2 photon characteristics and beach morphology. First, we corrected the ICESat-2 photons along satellite trajectories to the direction perpendicular to the coastline, and then preliminarily eliminated sea surface photons. Second, we combined the adaptive threshold OPTICS (Ordering Points To Identify the Clustering Structure) algorithm and the moving window filter to accurately extract sandy beach photons. Third, horizontal ranges of sandy beaches were determined by the quadratic polynomial model, and coastal slopes were estimated using a linear regression model. The proposed large-scale method for deriving beach slopes relies primarily on ICESat-2 photon counting light detection and ranging (LiDAR) data and auxiliary vector data, which does not require in-situ measurements. We applied this method to calculate coastal slopes for 212 sandy beaches with 1,297 profiles in New Zealand and conducted a validation using 1 m high-accuracy airborne Digital Elevation Model (DEM) data. Our results indicate that the inverted beach slopes from our method exhibit a high accuracy (root mean square error (RMSE) = 0.06, determination coefficient (R2) = 0.76). In the future, this method has a large potential for global applications using ICESat-2 data, serving as a valuable tool for estimating coastal slopes for sandy beaches worldwide.